Prediction of factors influencing the timing and prognosis of early tracheostomy in patients with multiple rib fractures: A propensity score matching analysis - Zhang, Bing; Li, Gong-Ke; Wang, Yu-Rong; Wu, Fei; Shi, Su-Qin; Hang, Xin; Feng, Qin-Ling; Li, Yong; Wan, Xian-Yao (Frontiers in Surgery, 2022)
Objective To investigate the factors affecting the timing and prognosis of early tracheostomy in multiple rib fracture patients.Methods A retrospective case-control study was used to analyze the clinical data of 250 patients with multiple rib fractures who underwent tracheotomy in the Affiliated Hospital of Yangzhou University from February 2015 to October 2021.According to the time from tracheal intubation to tracheostomy after admission, the patients were divided into two groups: the early tracheostomy group (within 7 days after tracheal intubation,ET) and late tracheostomy group(after the 7th day, LT).Propensity score matching(PSM) was used to eliminate the differences in baseline characteristics Logistic regression was used to predict the independent risk factors for early tracheostomy. Kaplan–Meier and Cox survival analyses were used to analyze the influencing factors of the 28-day survival.Results According to the propensity score matching analysis,a total of 174 patients were finally included in the study. Among them,there were 87 patients in the ET group and 87 patients in the LT group.After propensity score matching,Number of total rib fractures(NTRF)(P<0.001),Acute respiratory distress syndrome(ARDS)(P<0.001) and Volume of pulmonary contusion(VPC)(P<0.000) in the ET group were higher than those in the LT group.Univariate analysis showed that the patients who underwent ET had a higher survival rate than those who underwent LT(P=0.021).Pearson's analysis showed that there was a significant correlation between NTRF and VPC(r=0.369,P=0.001).A receiver operating characteristic(ROC)curve analysis showed that the areas under the curves were 0.832 and 0.804.The best cutoff-value values of the VPC and NTRF were 23.9 and 8.5,respectively.The Cox survival analysis showed that the timing of tracheostomy(HR=2.51 95%CI 1.12-5.57,P= 0.004) and age(HR=1.53 95% CI 1.00-2.05,P=0.042) of the patients had a significant impact on the 28-day survival of patients with multiple rib fractures.In addition,The Kaplan–Meier survival analysis showed that the 28-day survival of patients in the ET group was significantly better than that of the LT group,P=0.01.Conclusions NTRF,ADRS and VPC are independent risk factors for the timing and prognosis of early tracheotomy. A VPC≥23.9% and/or an NTRF≥8.5 could be used as predictors of ET in patients with multiple rib fractures.Predicting the timing of early tracheostomy also need prediction models in the future.